Penamaan Peralatan Rumah Tangga Tradisional Purwakarta Jawa Barat: Kajian Etnolinguistik: The Naming Of Sundanese Traditional Equipment In Purwakarta West Java: Etnolinguistics Approach - Irwan Syah; Susi Machdalena (Balai Bahasa Provinsi Papua, 2022)
The title of this research is “the naming of Sundanese Traditional Equipment in Purwakarta West Java: Etholinguistics Approach”. The purpose of this study was to describe the naming and use of Sundanese traditional equipment, especially at Ds. Wanakerta, Kec. Bungursari, Kab. Purwakarta. This research uses descriptive, the source of the data is taken using direct observastion with technique of listening and interviews with the informant. Based on the result of this research, there are many types of names for Sundanese traditional equipment in Purwakarta, namely 22 types of traditional equipment made of woven bamboo, 3 types made of stone, 4 types made of iron, 11 types made of wood, 3 types made by plastic, 8 types made of clay, 7 types made of alumunium, 3 types made by coconut shell, and 1 types made by copper. the most of Sundanese traditional equipment is woven bamboo with 22 types, because woven bamboo is very easy to find, easy to make, and the most important thing is very strong for long time used. Meanwhile, the are at least 1 type of Sundanese traditional equipment made of copper namely Tampolong. One of which is very rarely found as a copper base material in the Sundanese.